Education of students by means of national and cultural heritage - Terentyeva, Irina Vasilyevna; Chumarova, Lyubov Grigorevna; Fakhrutdinova, Anastasia Viktorovna; Mefodeva, Marina Anatolevna; Fassakhova, Guzel Rafkatovna (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The usage of national cultural peculiarities for university students, i.e. the native language (Russian and Tatar) folklore in teaching a foreign language at Kazan Federal University is considered. The research aimed to study the pedagogical potential of folklore of the native language in the training of future primary school teachers. The students of the 5th year of the Institute of Psychology and Education took part in the experiment. The work lasted for one year. The authors held the English language classes where they used the genres of the folklore (Russian and Tatar) for different educational purposes. The results of the study were the creation of some interesting exercises which helped students master their communicative skills, improve their pronunciation, grammar, and expand their vocabulary. The future primary school teachers actively participated in the research and creation of the exercises. Students were involved into the atmosphere of studying history and culture of the country they live in by reading, retelling, and analyzing fairy tales, myths, legends, baits. Translating folklore genres from their native language into a foreign one, students developed and improved their vocabulary, communication, and translation skills. According to the experience the future primary school teachers worked hard in self-development, they tried to find and use additional sources: dictionaries, literature, textbooks, encyclopedias and publications.